PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN AFEKTIF SEBAGAI VARIABEL INTERVENING (STUDI PADA KANTOR PT BESS FINANCE CABANG SEMARANG) - Gerard Indira Ramadhana; Intan Ratnawati (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of emotional intelligence on employee performance with affective commitment as an intervening variable. Employee performance is the most important factor, but there is a decline in performance at PT BESS Finance Semarang Branch. There is also a Research Gap which is the background of this research. The population in this study were employees of PT. BESS Finance Semarang Branch using a saturated sampling technique (census) in sampling with a sample size of 100 employees involved in this study. This study uses descriptive and quantitative analysis methods and uses multivariate analysis tools so that it can provide complex variable analysis results through the Smart Partial Least Square (PLS) 3.3.3 application program. The results of this study indicate that Emotional Intelligence has a positive and significant effect on affective commitment and also has a positive and significant effect on employee performance. Affective Commitment is proven to mediate the relationship between Emotional Intelligence and employee performance.